IDIOPATHIC CD4+ LYMPHOCYTOPENIA: A COMMON SYNDROME IN ARAB CHILDREN UNDER INVESTIGATION FOR IMMUNODEFICIENCY - G. Morgan; H. Al-Ansari; A. Moosa; A. Aghamohammadi; J. Crawley; V. Novelli (Acta Medica Iranica, 1996)
- the case definition for the syndrome of idiopathic CD4+ T-hymphocytopenia (1CL) includes a heterogeneity of disorders. As yet there have been very few published reports of chiUlren who meet the WHOjCDC criteria and it is unclear whether ICL is an acquired or inherited disorder. ChiUlren referred to a pacdiatric immunodeficiency unit between 1991 and 1993 for investigation of immunodeficiency were included if they met the above criteria. Six unrelated chiUlren from various locations in the Persian Gulf region met the criteria for ICL. 'Die parents of all six patients were related. These patients emphasise the heterogeneity of the syndrome and that low CD4+ counts may¬be present in early childhood. In view of the early onset of symptoms ICL may be congenital in some patients, parental consanguinuity suggests an autosomal recessive mode of inheritance.